ANALYSIS OF MODERN ETIOLOGICAL FACTORS OF PATHOLOGICAL ABRASION DEVELOPMENT OF HARD TISSUES OF TEETH (ACCORDING TO LITERATURE SOURCES) - Yu.P. Koval; V.M. Dvornyk; L.B. Yerys; Ya.V. Koval (Український стоматологічний альманах)
Relevance. Tooth abrasion is an inevitable consequence of their evolutionarily determined purpose of acquiring food through predation, detention, capture, grinding, chewing and swallowing. The mechanism of odontogenesis, according to which the amelogenesis of enamel ends with the death of ameloblasts before eruption, makes it impossible to recover enamel after damaging. Accordingly, any damage of any source is reflected on the hardest and oldest remains of creatures with teeth forever. Thus, tooth abrasion has a multifactorial origin and is based on diet and eating habits, oral hygiene, bruxism, brushing habits, xerostomia, anorexia, gastro-oesophageal reflex disease, vomiting, bulimia, and medications. Because enamel is the most wear-resistant tissue, the hardness and thickness of the enamel become evolutionary responses to environmental and dietary changes. In different periods of human development, there were certain, inherent in the time and territory of residence, taste preferences, eating habits, cooking methods, popular dishes. Constant acceleration, efforts to be on time everywhere, urbanization and industrialization have forced people to adapt, change their habits, including food. Fast food has become popular: chips, nuts, crackers and other snacks. Sour sauces and various salad dressings are added to them. A large selection of carbonated sweet drinks, or containing natural juices, gradually displace the habit of plain water drinking. On the other hand, modern fast-paced life causes increased nervous load, chronic stress, irritability and constant fatigue, which in turn affects the tone of the masticatory muscles. In addition, it is necessary to take into account the presence of somatic diseases, behavioral habits, individual characteristics of the bite, working conditions. Impact of numerous factors lead to changes of old hard tissues. Different types and forms of tooth abrasion are a great example of this. Among the non-caries lesions that develop after the eruption of permanent teeth, tooth abrasion is a common problem.